HOMOGENISASI DENSITAS FOTO VERTEBRAE THORACAL PROYEKSI ANTERO POSTERIOR (AP) DENGAN MENGGUNAKAN FILTER BAJI 7°, 10° DAN 15° - Amroji, Ali; Halimahtusyadiah, Halimahtusyadiah (JRI (Jurnal Radiografer Indonesia), 2021)
Background: The different thickness of the thoracic vertebrae between the top and bottom causes the radiograph to have uneven density. The use of heel effect anode in the examination of the thoracal vertebrae of the AP projection has not been able to even out the radiograph density, so it is necessary to use a tool in the form of a wedge filter. This study aims to find the correct angle of inclination of the wedge filter to produce a radiograph with a sufficiently even density between the top and bottom of the AP projection thoracic vertebrae. The wedge filter tested tilt angle of 7 °, 10 ° and 15 °. Methods: The research used quantitative methods, conducted from January to May 2018. The sample consisted of 4 volunteers and 10 radiographers as respondents. Results: The results showed that the examination of the thoracal vertebrae of the AP projection without using a filter obtained an average value of 2.50 from the respondents, while using a wedge filter with a tilt angle of 7 ° got a value of 2.80, with a tilt angle of 10 º got a value of 3.43 and with an angle of inclination. 15 º gets a score of 2.93, so it can be denied that the use of a wedge filter with an angle of 10º is able to produce a more even radiograph density between the top and bottom of the AP projection spine. Conclusions : To produce a more even radiograph density between the top and bottom of the thoracal vertebrae, the AP projection can be done using a wedge filter with an angle of 10°.